The design and operation of a membrane photobioreactor using Rhodopseudomonas palustris for simultaneous wastewater treatment and biohydrogen production - Kriek, Christi Gepke (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.